Adapting the Surface Integrity of High-Speed Steel Tools for Sheet-Bulk Metal Forming - Wolfgang Tillmann; Dominic Stangier; Alexander Meijer; Eugen Krebs; Alexander Ott; Timo Platt; Nelson Filipe Lopes Dias; Leif Hagen; Dirk Biermann (Journal of Manufacturing and Materials Processing, 2022)
New manufacturing technologies, such as Sheet-Bulk Metal Forming, are facing the challenges of highly stressed tool surfaces which are limiting their service life. For this reason, the load-adapted design of surfaces and the subsurface region as well as the application of wear-resistant coatings for forming dies and molds made of high-speed steel has been subject to many research activities. Existing approaches in the form of grinding and conventional milling processes do not achieve the surface quality desired for the forming operations and therefore often require manual polishing strategies afterward. This might lead to an unfavorable constitution for subsequent PVD coating processes causing delamination effects or poor adhesion of the wear-resistant coatings. To overcome these restrictions, meso- and micromilling are presented as promising approaches to polishing strategies with varying grain sizes. The processed topographies are correlated with the tribological properties determined in an adapted ring compression test using the deep drawing steel DC04. Additionally, the influence of the roughness profile as well as the induced residual stresses in the subsurface region are examined with respect to their influence on the adhesion of a wear-resistant CrAlN PVD coating. The results prove the benefits of micromilling in terms of a reduced friction factor in the load spectrum of Sheet-Bulk Metal Forming as well as an improved coating adhesion in comparison to metallographic finishing strategies, which can be correlated to the processed roughness profile and induced compressive residual stresses in the subsurface region.